The Personal Infinitive in Adverbial Clauses in Central American Spanish - Herrera Morera, Gisselle (2015)
This paper describes and analyzes, from a typological-functional perspective, personal infinitive structures in adverbial clauses introduced by a preposition + pronoun subject + infinitive [PSpI] in Central American Spanish to show that although there is not a trend to use this structure in this variety, it is an emerging phenomenon that could increase.